2020
DOI: 10.1021/acscatal.9b04840
|View full text |Cite
|
Sign up to set email alerts
|

Superior Catalytic Performance of Atomically Dispersed Palladium on Graphene in CO Oxidation

Abstract: Although substantial advances have been made in a few reactions of industrial significance over single-atom catalysts (SACs), the origin of the superior catalytic performance, the nature of the active sites, and the reaction pathways are still the subject of debate. Even for CO oxidation over SACs on nonreducible substrates, the understanding is limited. We investigated the performance of Pd atoms monodispersed on graphene (PdGr) in CO oxidation. Combining firstprinciples-based thermodynamics calculations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 97 publications
3
41
0
Order By: Relevance
“…The authors attribute the exceptional catalytic performance to the obviously reduced capability of the Au 1 SACs to dissociate H 2 in the catalytic process. Meng and colleagues have also tracked the origin of the superior CO oxidation performance of the isolated Pd atoms decorated graphene (PdGr) [ 101 ]. Combining DFT simulations and micro-kinetics modeling, the authors have confirmed that the positively charged PdGr can bind strongly with O 2 , acting as the reactive species to convert CO.…”
Section: Catalytic Applications Of the Isolated Reactive Centersmentioning
confidence: 99%
“…The authors attribute the exceptional catalytic performance to the obviously reduced capability of the Au 1 SACs to dissociate H 2 in the catalytic process. Meng and colleagues have also tracked the origin of the superior CO oxidation performance of the isolated Pd atoms decorated graphene (PdGr) [ 101 ]. Combining DFT simulations and micro-kinetics modeling, the authors have confirmed that the positively charged PdGr can bind strongly with O 2 , acting as the reactive species to convert CO.…”
Section: Catalytic Applications Of the Isolated Reactive Centersmentioning
confidence: 99%
“…This barrier is already more significant than the calculated E ad of O 2 (À1.81 eV); therefore, O 2 may desorb prior to dissociation. 34,39,78 As O 2 adsorption is more plausible than CO adsorption, Eley-Rideal-type pathways can only be initiated with the reaction between gaseous CO or CO in van der Waals complexes formed between CO and preadsorbed O 2 . 23 According to the symmetry of the molecular states of gaseous CO and O 2 , only the interactions between 5s of CO gaseous with the p* states of O 2 in the direction with O(O 2 )-C-O of B1201 is allowed, and the reaction may lead to direct formation of CO 2 .…”
Section: Conventional Revised Langmuir-hinshelwood Pathwaymentioning
confidence: 99%
“…8,9 Recently, considerable attention has been continuously paid to the controlled synthesis and application of heterogeneous transition metal SACs that inherit not only the merits of enzymes and metal complexes with each mono-dispersed transition metal atom as a reaction center for efficient chemical conversion, but also the advantages of heterogeneous catalysts for the reusability of the catalyst and easy product separation. [10][11][12][13][14][15][16] Many graphene-derived SACs of Fe, 8,9,[17][18][19][20][21][22][23][24][25][26][27][28] Ni, 29 Co, 18 Mn, 30 Pd, [31][32][33][34][35][36] Au, [37][38][39][40] Pt, [41][42][43] Ru, 44 etc., have been investigated and were proposed to be efficient in many processes of industrial significance. 45 Fe-Based SACs on graphene and graphenerelated materials were shown to be effective for the oxidation of arenes, 8 oxygen reduction, 9,[17]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations